Realismo científico modal - Diego Henrique Figueira de Melo (2020)
In this thesis I present a theory called Modal Scientific Realism. The most central aim is to solve the epistemics and metaphysicals problems regarding the entities known as possible worlds. Secondly, I also want to provide an interpretative support to Brian Ellis' Scientific Essentialism. This kind of essentialism holds that essential properties exist, but rejects an realistic approach to possible worlds. My theory has been developed based on the belief that if we accept modalities, we should also accept the discussion about possible worlds. Possible worlds problems arising from possibilty problems will be answered in due course in this research.